2019
DOI: 10.1038/s41531-019-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson’s phenome—traits associated with Parkinson’s disease in a broadly phenotyped cohort

Abstract: In order to systematically describe the Parkinson’s disease phenome, we performed a series of 832 cross-sectional case-control analyses in a large database. Responses to 832 online survey-based phenotypes including diseases, medications, and environmental exposures were analyzed in 23andMe research participants. For each phenotype, survey respondents were used to construct a cohort of Parkinson’s disease cases and age-matched and sex-matched controls, and an association test was performed using logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…In a recent paper from some members of this group, novel cross-sectional associations with PD were reported for migraine and epilepsy. 5 Here, we have not only replicated the association with epilepsy but also demonstrated a temporal relationship with incident PD. Whether the association is driven by epilepsy, chronic use of antiepileptic drugs or residual confounding remains to be determined.…”
Section: Discussionsupporting
confidence: 71%
“…In a recent paper from some members of this group, novel cross-sectional associations with PD were reported for migraine and epilepsy. 5 Here, we have not only replicated the association with epilepsy but also demonstrated a temporal relationship with incident PD. Whether the association is driven by epilepsy, chronic use of antiepileptic drugs or residual confounding remains to be determined.…”
Section: Discussionsupporting
confidence: 71%
“…In a recent paper from some members of this group, 'novel' cross-sectional associations with PD were reported for migraine and epilepsy 8 . Here we have not only replicated the association with epilepsy, but we have also demonstrated a temporal relationship with incident PD.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, there exists good epidemiological evidence to support a role for potentiallymodifiable exposures including pesticide exposure, head injury, and potentially protective factors such as smoking, and drinking alcohol or caffeinated drinks 5,6,7,8 . Various comorbidities, such type 2 diabetes, and prodromal symptoms are more common among individuals who are subsequently diagnosed with PD, including anosmia, anxiety, depression, constipation, REM sleep behaviour disorder (RBD) and erectile dysfunction 7,8 . There are several examples of approaches that are being used in research settings to model the risk of PD prospectively [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…To make matters more confusing, a meta-analysis of fourteen case-control studies concluded that T2DM was associated with a reduced risk of PD (summary odds ratio 0.75) [36]. A very large, recent, cross-sectional study using self-reported information also found T2DM to be negatively associated with PD [37]. However, whilst cohort studies may be prone to biases as outlined above, cross-sectional and retrospective case-control studies may have additional design issues that bias effect estimates.…”
Section: T2dm Is Associated With An Increase In the Risk Of Pdmentioning
confidence: 99%